The Relationship between Mindfulness and Authentic Happiness in Young Women with Father Absence Caused by Parental Divorce - Afifah Nisa Fauziah; Ratna Syifa'a Rachmahana (LPPM IAIN Parepare, 2024)
Authentic Happiness is a dream for every human being. However, there are still those who have not felt Authentic Happiness due to father absence caused by parental divorce. This is because children put their happiness point on the family. The occurrence of divorce has a negative impact on the emotional side. It was found that women feel emotions more intensely than men. Therefore, the purpose of this study is to empirically determine the relationship of Mindfulness to Authentic Happiness in early adult women who experience father absence due to parental divorce. This study involved 142 respondents as research subjects. The research design used in this study is to use a quantitative approach with a correlational method. This study uses Pearson's Product Moment correlation analysis technique which results in a positive relationship between Mindfulness and Authentic Happiness in early adult women who experience father absence due to parental divorce. The implication of this research is that striving for happiness in negative conditions can be done by increasing mindfulness.